NDRG4 in gastric cancer determines tumor cell proliferation and clinical outcome. Issue 6 (24th March 2018) - Zhang, Zixi; She, Junjun; Yang, Jingyi; Bu, Xin; Ji, Gang; Zhu, Shaojun; He, Shuixiang; Chu, Dake
Abstract : As a novel candidate tumor suppressor, NDRG4 is largely unstudied in human malignancies. In this study, we investigated the protein expression level of NDRG4 in gastric cancer and its association with outcome of patients. In the present study, we recruited 286 patients with gastric cancer and investigated the protein and mRNA expression of NDRG4 in cancer and adjacent normal specimens by immunohistochemistry assay and real‐time PCR. The association of NDRG4 level with clinicopathological characteristics was investigated by appropriate statistical analysis. NDRG4 overexpression and knockdown cell lines were established in order to detect its impact on proliferation and apoptosis. Significant decreased protein and mRNA expression of NDRG4 was found in gastric cancer, compared with adjacent normal specimens. Besides, it was found that NDRG4 protein expression in gastric cancer was significantly associated with tumor differentiation, invasion, metastasis, and stage. Patients with tumors of decreased NDRG4 level were more likely to have unfavorable disease‐free and overall survival, in both univariate and multivariate analysis. In addition, overexpression of NDRG4 suppressed cell proliferation of gastric cancer cells in vitro; conversely, the proliferation of gastric cancer cells were enhanced by knockdown of NDRG4. These results proved for the first time that NDRG4 could be a potential tumor suppressor and prognostic marker of gastric cancer.